To Study the Iodine Concentration of Mothers’ Consumed Salt, Water, and Staple Food in the Neonatal Screening Program of Rural and Urban Vidarbha Region - Ankita Kondhalkar; Meghali Kaple; Ranjit S. Ambad; Archana Dhok; Ashsish Anjankar (Journal of Pharmacy and Bioallied Sciences)
Background: This study aimed to examine the iodine concentration in the food items consumed by mothers participating in neonatal screening programs in both areas of the Vidarbha region. A developing fetus relies on a consistent supply of iodine for proper brain and body development. During pregnancy, only the mother can provide the necessary iodine levels. If the mother is iodine-deficient, the child will also lack this essential nutrient. Severe deficiency in the mother can lead to significant stunting of the child’s brain and body, potentially preventing normal walking, talking, or cognitive function. Even if the mother’s deficiency is mild, the child can still be adversely affected, even if they appear healthy at first glance. The detrimental effects on brain development may manifest later in life as poor academic performance and difficulties in managing daily tasks. Material and Method: The present cross-sectional research will be performed in collaboration with the Departments of Biochemistry, Obstetrics and Gynecology, Community Medicine, and Pediatrics at Jawaharlal Nehru Medical College Sawangi (Meghe) Wardha, along with Datta Meghe Institute of Medical Science (Deemed University) in Maharashtra, India. Mothers who gave birth agreed to participate by providing written consent for the study. Results: The average iodine concentrations are quite similar across all sources, though hand pumps show slightly more variability. Different staple foods contain varying levels of iodine, with some foods (like pulses) exhibiting a lot of variation, while others (like rice and potatoes) are more consistent in their iodine content. Conclusion: The current study is a hospital-based investigation aimed at screening neonates for congenital hypothyroidism (CH) and does not reflect the broader population. To identify CH, screening of neonates will be conducted within the study area, providing a representative view of the condition. The clinical and pathological effects of CH are subtle and often remain unnoticed. Our findings suggest that the prevalence of iodine reflects dietary quality, educational background, and socioeconomic status, all of which can influence growth and development. There are various factors contributing to CH and inadequate fetal growth beyond low iodine levels, which can disrupt thyroid function. The study indicates that iodine levels are indicative of dietary quality as well as educational and social statuses, potentially impacting growth and development through both dietary deficiencies and other factors.